Kajian Hilirisasi Kelapa dan Sawit Indonesia Berdasarkan Produktivitas dan Sifat Fungsional - Nurhayati Nurhayati (UNEJ e-Proceeding, 2018)
Coconut and palm are Indonesian commodities that has great potential.Indonesia is first rank as a coconut producer and the largest palm producer in the worldafter Malaysia. This article examines the potential downstream of Indonesian palm oiland coconut based on their productivity and functional properties both health functionaland technical functional. Indonesian productivity of coconut during the last five years(2011-2015) decreased from 0.841 million ton / million Ha in 2011 to 0.829 million ton /million Ha in 2015. The Indonesia's productivity of palm oil was lower than Malaysia'sproductivity up to one-third. However, the area of Indonesia's palm plantations was four(4) times bigger than Malaysia. The functional value of coconut oil is the content of lauricacid as a medium chain fatty acid so coconut oil is important as energy intake non starch.The functional value of palm oil is the content of beta carotene as an antioxidant so palmoil is not easily damaged technically.